High Performance Single Carrier Schemes for Massive MIMO Systems - Madeira, João Falé de Carvalho (2019)
As the demands for faster and cheaper telecommunication systems continue to grow, so to do the demands for more efficient and secure systems. There have been several solutions proposed, with the most commonly accepted ones employing Massive Multiple Input, Multiple Output (mMIMO), featuring large arrays of antennas. The downside of these systems lies mainly in the need for computationally heavy channel equalization algorithms and the high hardware requirements, namely due to the need of many Power Amplifiers (PAs), Analog-to-Digital Converters (ADCs) and Digital-to-Analog Converters (DACs). This work analyses receivers that can handle these downsides, beginning with the low complexity equalization receivers Maximal-Ratio Detector (MRD) and Equal-Gain Detector (EGD), that can lower the equalization’s computation time. Then a Singular Value Decomposition (SVD) receiver is studied, with a proposed interleaving scheme to allow for equal performance on all streams, combined with a scheme for estimating and cancelling the non-linear distortion to reduce the impact of cheaper and more powerefficient PAs. These receivers are then improved with the introduction of an error correcting convolutional code. Lastly, it is demonstrated that the SVD receiver can be appealing as a solution for Physical Layer Security (PLS) in mMIMO systems.